Kryzys w Mali jako wyzwanie dla wspólnej polityki zagranicznej, bezpieczeństwa i obrony Unii Europejskiej w latach 2012-2014 - Paterek, Anna (Rocznik Integracji Europejskiej, 2015)
This paper explores the role played by the EU in addressing the crisis in Mali. The analysis briefly covers the causes and the outbreak of the crisis, the Frenchled intervention and the role of regional organisations and the UN’s response. The aim is to explore the evolution and humanitarian consequences of the Malian crisis with particular concern for the role played by the EU. The paper concludes with a brief analysis of the limitations of the EU’s Common Security and Defence Policy and the lack of political will to generate a concrete fast response as in the case of Mali.